1985
DOI: 10.1017/s000335610002780x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of milk substitute concentration upon the intake, digestion and growth of calves

Abstract: A total of 40 individually-penned British Friesian male calves were offered milk substitutes ad libitum from 2 days until 12 weeks of age. Ten milks were reconstitued from either liquid or spray-dried skim milk and a fat-filled (500 g fat per kg) powder and contained 80, 110, 140, 170 or 200 g dry matter (DM) per kg liquid. A further six calves were used in a randomized-block experiment to measure the digestibility, absorption and retention of the diets containing 80, 140 and 200 g DM per kg.There are no signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
2
3

Year Published

1985
1985
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
2
13
2
3
Order By: Relevance
“…The total water intakes were similar for the calves given milks containing 200, 230 and 260 g DM per kg.The linear relationship of DM intake to DM concentration of the milk substitute suggested a lower level of intake in the present experiment, than was observed in a previous experiment (Ternouth, Stobo, Roy and Beattie, 1985b) when the milk concentrations were lower and drinking water was not available. The live-weight gain and dry-matter and water intakes of calves offered milk substitute diets at high concentrations.…”
contrasting
confidence: 66%
See 1 more Smart Citation
“…The total water intakes were similar for the calves given milks containing 200, 230 and 260 g DM per kg.The linear relationship of DM intake to DM concentration of the milk substitute suggested a lower level of intake in the present experiment, than was observed in a previous experiment (Ternouth, Stobo, Roy and Beattie, 1985b) when the milk concentrations were lower and drinking water was not available. The live-weight gain and dry-matter and water intakes of calves offered milk substitute diets at high concentrations.…”
contrasting
confidence: 66%
“…The linear relationship of DM intake to DM concentration of the milk substitute suggested a lower level of intake in the present experiment, than was observed in a previous experiment (Ternouth, Stobo, Roy and Beattie, 1985b) when the milk concentrations were lower and drinking water was not available. When the concentrations of the DM were re-calculated to take into account the quantity of drinking water consumed, the relationships between DM intake and adjusted DM concentration for the two experiments were similar.…”
contrasting
confidence: 66%
“…Preliminary trials indicated that the YAF would not have survived on chopped oaten hay alone (see Munn and Dawson, 2003a). Assuming a milk-DM digestibility of 95% (Penning et al, 1977;Roy, 1980;Ternouth et al, 1985), the apparent digestibility of DM from the chopped oaten hay alone (i.e. excluding milk) by the YAF kangaroos was just 34.2±3.1%, significantly lower than that by weaned or adult kangaroos (Table·3).…”
Section: Forage Intake and Apparent Digestionmentioning
confidence: 99%
“…However, as noted above, the YAF also received a small amount of artificial milk with the chopped oaten hay. Assuming a milk-N digestibility of 95% (Penning et al 1977;Roy 1980;Ternouth et al 1985), the apparent digestibility of N by the YAF from the oaten forage alone was just , significantly lower than that 33% ‫ע‬ 7% by the weaned or mature female kangaroos ( ; Table 4). P !…”
Section: Dietary N Intake Apparent N Digestibility and N Balancementioning
confidence: 98%
“…However, P 1 0.05 the YAF on this diet also received artificial milk (80 mL d Ϫ1 ), because preliminary trials indicated that the YAF would not have survived on chopped oaten hay alone (see Munn and Dawson 2003b). Assuming a milk-DM digestibility of 95% (Penning et al 1977;Roy 1980;Ternouth et al 1985), the apparent digestibility of the DM from the chopped oaten hay forage (without milk) by the YAF was just , signif-34% ‫ע‬ 2% icantly lower than that by weaned or adult kangaroos (Table 3).…”
mentioning
confidence: 99%